Money and the Measurement of Total Factor Productivity - Diewert, W. Erwin; Fox, Kevin J. (Journal of Financial Stability, 2019)
Firms have greatly increased their cash holdings since the mid-1990s. These holdings have an opportunity cost; i.e., allocating firm financial capital into monetary deposits means that investment in real assets is reduced. Traditional measures of Total Factor Productivity (TFP) do not take into account these holdings of monetary assets. Given the recent large increases in these holdings in the U.S. and other advanced economies, it is expected that adding these monetary assets to the list of traditional sources of capital services will reduce the TFP of the business sector. We measure this effect for the U.S. corporate and non-corporate business sectors.